Questions and Answers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Hestia Inter, Brussels, Belgium, responds to a reader from Niger who asks, 'Could you advise us regarding decorticatingsesame?' SPORE: 'The hay seeds of sesame are rich in oil, proteins, calcium and phosphorus. Their use is inhibited by a...